Orange-fleshed sweet potato-wheat composite breads : physico-chemical, sensory and nutritional quality - madjaliwa@yahoo.fr (University of Pretoria, 2013)
Dissertation (MSc (Food Science and Technology))--University of Pretoria, 2012.